Risks of coastal storm surge and the effect of sea level rise in the Red River delta, Vietnam - James E. Neumann; Kerry A. Emanuel; Sai Ravela; Lindsay C. Ludwig; Caroleen Verly (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper considers the impact of sea level rise and storm surge on the Red River delta region of Vietnam an area already known to be highly vulnerable to coastal risks. By combining a range of sea level rise scenarios for 2050 with the simulated storm surge level for the 100-year storm surge, we analyze permanently inundated lands and temporary flood zones. As is well-established in the literature, sea level rise will increase the risk of storms by raising the base sea level from which surge is launched, but our method quantified the increase for disaster planning and vulnerability assessment purposes. Our analysis finds that sea level rise through 2050 could increase the effective frequency of the current 100-year storm surge, which is associated with a storm surge of roughly five meters, to once every 60 years. Approximately 10 percent of the Hanoi region's GDP is vulnerable to permanent inundation due to sea level rise, and more than 40 percent is vulnerable to periodic storm surge damage consistent with the current 100-year storm. We conclude that coastal adaptation measures, such as a planned retreat from the sea, and construction of a more substantial seawall and dike system, are needed to respond to these threats.
Keywords: Q54; Q56; Q51; 330; sea level rise; storm surge; tropical cyclone risk; flood risk; South East Asia